IMPROVEMENT OF CADETS’ LANGUAGE TRAINING IN THE FRAMEWORK OF ACADEMIC COOPERATION - Pashchuk, Y.; Kamentsev, D.; Pasichnyk, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The paper focuses on developing of cadets’ language training (CLT) in the professional military education (PME) schools in the framework of the Ukraine-NATO and Ukraine-EU academic military cooperation. It identifies an urgent need in improving the language training of cadets due to the contradictions between the required level of language proficiency for future officers (level 2 according to STANAG 6001) and insufficient foreign language skills of a considerable number of graduates from Ukrainian PME schools. Academic military cooperation is considered as important area of activities to domestic and partner-nation PME schools. Its main objective is to ensure integration of national military education in the global educational space. Such cooperation is mutually beneficial and allows Ukraine to develop capacity to influence the international security system; improve the Ukrainian Army operational capabilities and acquire interoperability with NATO forces. The main means to achieve these goals are implementing the Euro-Atlantic standards, perfecting the Ukrainian servicemen training, including improving CLT. The paper examines the key directions of the Ukrainian academic military cooperation with NATO and EU in developing CLT in the framework of adopted programs. It describes main aspects of these projects and their implementation mechanisms as well as key advantages, opportunities and achievements of such cooperation. Based on the effectiveness assessment of existing academic military cooperation programs, it was concluded that they have a positive impact on improving the CLT with use of open access to training resources, intellectual achievements, modern training technologies and best practices of partner countries. The main tasks for further development of the academic military cooperation include perfecting support to CLT, improving professional development of the faculty and implementing innovative forms of education.